The controlling nutritional status score and risk factors associated with malnutrition in patients with acute ischemic stroke - Chen, Yuanyuan; Yang, Hongyan; Lan, Meijuan; Wei, Hui; Chen, Yanqin (Frontiers in Neurology, 2023)
Objectives: Malnutrition is an independent risk factor for poor outcomes in acute ischemic stroke (AIS) patients. The controlling nutritional status(CONUT) score can provide information for nutritional management in AIS patients. However, the risk factors of CONUT have not been established yet. We investigate the CONUT score of AIS patients and explore the risk factors of the CONUT. Methods: We retrospectively reviewed the data of consecutive AIS patients recruited in the CIRCLE study. The CONUT score, Nutritional Risk Screening 2002, Modified Rankin Scale, National Institutes of Health Neurological Deficit Score (NIHSS), and demographic data were gathered from medical records within 2 days after admission and were examined by Chi-squared tests. Logistic regression analysis was used to explore the risk factors of the CONUT in AIS patients. Results: A total of 231 AIS patients completed the study, with a mean age of 62.32 ± 13.0 years. The mean NIHSS was 6.77±3.8, and 41(17.7%) had hyperlipidemia. In the aspect of nutritional assessment, 137(59.3%) AIS patients had high CONUT scores, 86(37.2%) AIS patients with low or high BMI, and 117(50.6%) AIS patients with NRS-2002 scores below 3. Chi-squared tests showed that age, NIHSS, Body Mass Index (BMI), and hyperlipidemia were associated with the CONUT (P＜0.05). Logistic regression analysis showed that low NIHSS scores (OR=0.055 95% CI: 0.003-0.893), Youths (OR=0.159 95% CI: 0.054-0.469), hyperlipidemia (OR=0.303 95% CI: 0.141-0.648) were independently associated with lower CONUT score (P＜0.05), BMI was not shown to be independently associated with the CONUT. Conclusions: More than half of AIS patients had the risk of malnutrition. Age and neurological deficits are the risk factors of nutritional control. Hyperlipidemia is a protective factor of the CONUT. NRS-2002 and BMI may not affect the nutritional control in AIS patients.